A Note on the Time. - Sinister, Dexter (Art Journal)
The article discusses the concept of time as a point that is captured or stamped, focusing on how the use of time signatures in computers rely on a computer code called Network Time Protocol (NTP) to synchronize their time signatures. The author explores the empiricism of philosophers David Hume and William James and their respective acceptance or rejection of atomized time. Topics include the counting of time by clocks, the book "From Sundials to Atomic Clocks: Understanding Time and Frequency," by James Jespersen and Jane Fitz-Randolph, and the article "Socialism: A Life Cycle," by Régis Debray in number 46 of "New Left Review."